Wage gap and stock returns: Do investors dislike pay inequality? - Dittmann, Ingolf; Montone, Maurizio; Zhu, Yuhao (Journal of Corporate Finance, 2023)
Recent research shows that a high wage-gap between managers and workers identifies better-performing firms, but the stock market does not seem to price this information. In this paper, we show that not all investors neglect pay inequality. Using a unique data set on German firms' employee compensation, we find that the mispricing of the wage gap is driven by limits to arbitrage. Specifically, some investors seem to bid up low-wage-gap stocks for non-monetary reasons, thus exhibiting a preference for low pay-inequality. The results suggest that firms with equitable pay schemes are rewarded with a lower cost of capital.